1989
DOI: 10.2527/jas1989.673738x
|View full text |Cite
|
Sign up to set email alerts
|

Utero-Placental Transfer of Octanoic, Palmitic and Linoleic Acids during Late Gestation in Gilts

Abstract: The transfer across the swine uterus and placenta of [1-14C]octanoic acid, [9,10(n)-3H]palmitic acid and [1-14C]linoleic acid was studied in five gilts and their fetuses during late gestation following a single bolus injection. Only trace amounts of labeled fatty acids were found in fetal plasma lipid. The highest fetal plasma lipid values were less than 1.2% of the peak maternal values. The concentration of plasma free fatty acids (FFA) and fatty acid profiles in the umbilical artery (FA) and vein (FV) and ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 15 publications
3
21
1
Order By: Relevance
“…This is consistent with the report that modulation of dietary fatty acids of the sow milk influences the fatty-acid composition of piglets' liver and adipose tissue (Lauridsen and Jensen, 2007). In respect to manipulation of the pig diet during gestation, some authors reported that only a small amount of the dietary fatty acids can be transferred to the foetus (Thulin et al, 1989;Ramsay et al, 1991). However, a later study demonstrated that maternal dietary fat has a significant input in the fatty-acid composition of plasma and tissues in the developing foetus (Leskanich and Noble, 1999).…”
Section: -Desaturasesupporting
confidence: 91%
“…This is consistent with the report that modulation of dietary fatty acids of the sow milk influences the fatty-acid composition of piglets' liver and adipose tissue (Lauridsen and Jensen, 2007). In respect to manipulation of the pig diet during gestation, some authors reported that only a small amount of the dietary fatty acids can be transferred to the foetus (Thulin et al, 1989;Ramsay et al, 1991). However, a later study demonstrated that maternal dietary fat has a significant input in the fatty-acid composition of plasma and tissues in the developing foetus (Leskanich and Noble, 1999).…”
Section: -Desaturasesupporting
confidence: 91%
“…L -1 ) and concluded that FFA are not significantly extracted by the uterus. Only trace amounts of labelled fatty acids were found in foetal plasma lipids following the injection of labelled fatty acids to anaesthetised sows [59], and some direct transfer of maternal fatty acids to the foetus was demonstrated in pigs [22,52]. In the present experiment, FFA were extracted by the uterus only when their levels were elevated.…”
Section: Glycerolmentioning
confidence: 74%
“…Measurements of blood substrate levels in pig foetuses were made either from the umbilical blood during a caesarean operation in anaesthetised animals [1,9,35,[46][47][48][49]59], or from foetuses with catheters implanted in the jugular vein or in the carotid artery [20,44,45]. An attempt of measuring substrate balances across the foetoplacental unit was also performed in the gilt [10].…”
Section: Discussionmentioning
confidence: 99%
“…Their uptake does not represent a significant energy source for the gravid uterus of sheep [70], cows [64], mares [64] or sows [10,61]. In experiments involving ewes [71,72] or sows [73,74] injected with labelled fatty acids, only trace amounts of these fatty acids crossed the placenta during late gestation.…”
Section: Fatty Acids Ketone Bodies and Glycerolmentioning
confidence: 99%